إدارة الأزمات المبكرة في ظل وباء "کوفيد-19" بالشرکات الكويتية - الفضلي، خليل جودة مبارك; الشمري، محمد هبر (جامعة الزقازيق - كلية التجارة, 2021)
يعد الاستعداد الإداري هاجس مستديم للشركات لإدارة الأزمات، وتتفاقم حدة هذا الاستعداد والقلق أثناء فترات التوتر الشديد، والتي تنجم عن أزمات خارجية، وتقوم الدراسة الحالية بتحليل بعض الخبرات في إدارة أزمة كورونا للاستفادة منها في الشركات الكويتية تجاه أكبر أزمة حدثت حتى يومنا هذا، ونقصد بها جائحة كوفيد (19) (وباء الكورونا) في أواخر 2019م وصولاً إلى 2020، وستقوم بالتحليل من خلال الاستناد إلى نظرية المسح البيئي والخلل الوظيفي والإداري ثم نعرج على توثيق الأفعال الصادرة عن الإدارة حيال حالات الفزع المتعددة المرتبطة بالصحة العامة ويغطي ذلك (وباء سارز)، وأنفلونزا الخنازير، ثم الكوفيد (19)(الكورونا)، وتشير النتائج إلى أن بعض الشركات العالمية شهدت حالة من الركود تكاد تصل إلى صفر بسبب جائحة كورونا، وكان من المفروض أن يدق ذلك جرس الإنذار لدي مديري الشركات لكي يستعدوا لحدوث سيناريوهات تنذر بكوارث مالية كتلك التي حدثت فعليا في أوائل 2020م، وفشلت فرق الإدارة في هذه الشركات في التعلم من هذه الأزمة التي مست الصحة العامة العالمية، وعجزت عن وضوح الحلول والاستراتيجيات لتلك الأزمة في شركاتهم، وركزوا على تهديدات أخري أقل خطورة خلال توزيع العوائد المالية المتمثلة في الأرباح واقتناص الفرص المالية.
Administrative preparedness is a constant concern for companies to manage crises, and this readiness and anxiety are exacerbated during periods of severe tension, which are caused by external crises, and the current study analyzes some experiences in managing the Corona crisis to benefit from them in Kuwaiti companies towards the largest crisis that has occurred to this day, and we mean it. The Covid pandemic (19) (Corona epidemic) from the end of 2019 until 2020, and we will analyze by relying on the theory of environmental scanning and dysfunction and management, and then we come to document the actions issued by the administration regarding the multiple panic cases related to public health and this covers (the Sars epidemic), And swine flu, then covid (19) (Corona), and the results indicate that some global companies witnessed a state of almost zero recession due to the Corona pandemic, and this was supposed to sound the alarm bell for company managers in order to prepare for the occurrence of scenarios that warn of financial disasters such as these Actually that occurred in early 2020 AD, and management teams in these companies failed to learn from this crisis that affected global public health, and were unable to clarity solutions and strategies for that crisis in their companies, and they focused on it Other less risky deeds in distributing financial returns are profits and seizing financial opportunities.
Keywords: إدارة الأزمات -- الأمراض الوبائية -- فيروس كورونا "كوفيد-19" -- الشركات الكويتية